Nationwide drug-dispensing data reveal important differences in adherence to drug label recommendations on CYP2D6-dependent drug interactions - Mannheimer, Buster (Blackwell Science Inc, 2010)
AIMS: The study aimed to investigate the clinical adherence to drug label recommendations on important drug–drug interactions (DDIs). Dispensing data on drug combinations involving selective serotonin reuptake inhibitor (SSRI) antidepressants could help to identify areas for intensified medical education. METHODS: This was a retrospective, cross-sectional analysis of individual dispensing data regarding all individuals ≥15 years old in Sweden. The study analysed the prescribing and dispensing of CYP2D6 drugs (metoprolol, donepezil, galantamine, codeine, tamoxifen) together with CYP2D6-blocking SSRIs (paroxetine/fluoxetine) or SSRIs without significant CYP2D6 inhibition (citalopram/escitalopram/sertraline), and the related prescribing of CYP2D6-independent comparator drugs (atenolol, rivastigmine, propoxyphene, anastrozole). Odds were calculated between each CYP2D6 drug and the corresponding comparator drug in patients on fluoxetine/paroxetine and citalopram/escitalopram/sertraline, respectively. The odds ratio (OR) was calculated by dividing the obtained odds in patients on fluoxetine/paroxetine by the corresponding odds in patients on citalopram/escitalopram/sertraline. RESULTS: Compared with patients that were dispensed citalopram/escitalopram/sertraline, patients dispensed fluoxetine/paroxetine had lower prescribing rates of metoprolol (adjusted OR 0.80; 95% confidence interval 0.76, 0.85), donepezil (0.65; 0.49, 0.86) and galantamine (0.58; 0.41, 0.81). In contrast, the use of prodrugs codeine (compared woth propoxyphene) or tamoxifen (compared with anastrozole) was similar among patients on fluoxetine/paroxetine and citalopram/escitalopram/sertraline (adjusted OR 1.03; 0.94, 1.12 and 1.29; 0.96, 1.73, respectively). CONCLUSIONS: Clinically important DDIs that are associated with impaired bioactivation of prodrugs might be more easily neglected in clinical practice compared with DDIs that cause drug accumulation and symptomatic adverse drug reactions.